(untitled) (Research, Society and Development, 2022)
The Teaching of Science and inclusive education is something much discussed, but it is still noted that much must be done so that inclusion in the classroom actually occurs. Therefore, we sought to answer the problem of the research that is based on the teaching methodologies adopted for Science Teaching. Thus responding to the objectives of the work, where through this some methodological practices used for teaching science in the classroom and ways to promote inclusion were described. For this, an exploratory qualitative research methodology was chosen, having as analysis instruments the bibliographic survey in dissertations, theses, articles, books and online publications. Therefore, during the accomplishment of this research it became evident that Science Teaching can be taught with several works. These can be dynamic, with differentiated, innovative and creative methodologies, making the subject interesting for students. Science Teaching also presents complex themes that are often not understood by students, but it is possible to provide quality education that meets everyone’s needs.